Using the teaching techniques of 5Es (engage, explore, explain, elaborate and evaluate) in teaching technology integrated science subjects : a survey at selected international schools in Selangor - Mohamed Rajab Haji (International Islamic University Malaysia, 2014)
The purpose of this research was to assess the extent to which Secondary Science Teachers in the state of Selangor-Malaysia used teaching techniques of Engage, Explore, Explain, Elaborate and Evaluate (5Es) in technology integrated science subjects. It examined (i) the relationship between 5Es and students‟ intrinsic motivation; and (ii) the relationship between 5Es and metacognition among selected secondary school students in Selangor. The theoretical framework utilized constructivists teaching and learning using 5Es model as proposed by Bybee in 2006. A sample of 500 students was randomly selected from four international secondary schools to reflect their science teachers approach in teaching. The selected schools were: Sayfol International School, International Islamic School Malaysia, Fair View International School and International Darul Huffaz. The study employed a survey method. Data was collected using self-administered questionnaires. The findings of the study revealed that most of the teachers utilized 5Es in their teaching methodology. The study further found out that there was a positive relationship between 5Es and intrinsic motivation. The results indicate that there exist a relationship between 5Es and metacognition. The implications of these findings indicate the importance of using 5Es teaching techniques as it enhances motivation to learn and awareness of learning strategies among students. Therefore, it is recommended that, Teacher Training Institutions inculcate the 5Es model so as to translate them in teaching sciences in Secondary Schools.